PENGAWETAN IKAN BANDENG (CHANOS-CHANOS FORSK) TINGGI LISIN DENGAN PENGASAPAN CAIR DAN PENAMBAHAN SENYAWA ANTI MIKROBIA DAN ANTIOKSIDAN DARI DAUN SIRIH TINGGI OLEORESIN (piper bitttle Linn) DALAM BENTUK KAPSUL - Wahyuningsih Wahyuningsih (Universitas Diponegoro, 2012)
Abstracl On this reaseach have observed liquid smoke's ability to pursue microbe activity, antimicrobe and antioxidant compounds in betel oleoresin, give preservation by purse microorganism's growth on chanos-chanos forsk. Fis submerge process by liquid smoke with bettle oleoresin submerge on presmoking, give optimum result in preserve time eight weeks lysine value 26,56 mg/100 g, with TVB value 7,66 mgN/100 g and microorhanism 9,5 x 12 CFU/g. Reach on submerge with liquid smoke 4 % concentration, during 15 minutes, and submerge with liquid smoke 4% concentration during I0 minutes. Result above have contribution with sensoric examine of rather hard to hard texture and very like flavor Keywords : Liquid Smoke - oleoresin sirih- Bandeng Fish